Near‐Field Mediated 40 nm In‐Volume Glass Fabrication by Femtosecond Laser. Issue 4 (17th December 2021) - Yan, Zhi; Gao, Jichao; Beresna, Martynas; Zhang, Jingyu
Abstract: Nanofabrication techniques have significantly impelled the development of nanomechanics and nanophotonics by making nano‐precision material processing routine. Although widely employed, current sub‐100 nm nanofabrication approaches based on focused particles or light are limited to surface modification. Here, an optical in‐volume fabrication approach that enables 3D glass processing with a spatial resolution down to 40 nm is demonstrated. Such an approach is based on the formation of a single nanoslit structure induced by femtosecond laser pulses. Spatially‐variant nanopatterns with uniform line‐widths are then formed by a near‐field mediated intensity redistribution of incident light. The redistribution of electromagnetic field induced by the presence of the nanoslit leads to a positive‐feedback self‐assembly process. The self‐assembly process allows achieving spacing one order of magnitude smaller than the laser beam size. In addition, a tilted ablation front that results in the generation of structures with curved morphology is revealed. The proposed approach enables 3D patterning with a lateral spacing down to 200 nm and 5D optical data storage with an equivalent capacity of 7.2 TB per disk, demonstrating its feasibility for 3D nanoscale processing in bulk materials. Abstract : Single nanoslit (SNS) with a spatial resolution of 40 nm is processed by femtosecond laser direct writing. This is caused by a near‐field mediated intensity redistribution of incident light, which is further verified in SNS spacing experiment and bifurcation phenomenon. Two applications are implemented, that is, in‐volume spatially‐variant nanofabrication and high capacity optical data storage.